Giải các phương trình: (x^2+x+1)^2=3(x^4+x^2+1)

Giải các phương trình: (x^2+x+1)^2=3(x^4+x^2+1)

2 bình luận về “Giải các phương trình: (x^2+x+1)^2=3(x^4+x^2+1)”

  1. (x^2+x+1)^2=3(x^4+x^2+1)
    <=> (x^2+x+1)^2=3(x^4+2x^2+1 – x^2 )
    <=> (x^2+x+1)^2=3(x^2-x+1)( x^2 + x + 1 )
    <=> (x^2+x+1)^2-3(x^2-x+1)( x^2 + x + 1 ) = 0
    <=> ( x^2 + x + 1 )( x^2 + x + 1 – 3x^2 + 3x – 3 ) = 0
    <=> ( x^2 + x + 1 )( -2x^2 + 4x – 2 ) = 0
    Do x^2 + x + 1 = ( x + 1/2 )^2 + 3/4 >= 3/4 \ne 0
    => -2x^2 + 4x – 2 = 0
    <=> x^2 – 2x + 1 = 0
    <=> ( x-1)^2 = 0
    <=> x-1=0
    <=> x=1
    Vậy S={1} 
     

    Trả lời

Viết một bình luận

Câu hỏi mới